Implementasi CMS Prestashop Pada Toko Ira Shop Bag Untuk Meningkatkan Transaksi Penjualan Tas dan aksesoris - Dalimunthe, Annisa Putri; Syavitri, Tiara; Harahap, Syaiful Zuhri (Journal of Student Development Information System (JoSDIS), 2025)
The implementation of PrestaShop CMS in Irashopbag stores aims to increase sales transactions of bags and accessories by taking advantage of the features offered by this platform. PrestaShop, as an open-source content management system (CMS), provides a wide range of tools that allow for efficient product management, payment processing, and shipping arrangements. By integrating PrestaShop, Irashopbag can expand its marketing reach and improve operational efficiency, making it easier for consumers to find and buy products anytime and anywhere. This is in line with the digitalization trend that increasingly dominates the e-commerce market today.Through this research, it is hoped that Irashopbag can overcome the obstacles faced in traditional marketing methods that tend to be limited. The implementation of an online sales system using PrestaShop will not only reduce promotional costs but also increase the accessibility of product information for consumers.